Evaluation of diallelic STR markers with inter-population allelic database for their usefulness in paternity trios in the Central Indian population - Hirak Ranjan Dash; Kamayani Vajpayee; Radhika Agarwal; Anubha Gang; Ritesh Shukla; Ankit Srivastava (Annals of Human Biology, 2021)
Background Most of the forensic DNA laboratories have migrated to new generation STR kits of 6 dye chemistry with more than 20 autosomal STRs. The population-specific databases of such STR markers are lacking in many regions. Aim To evaluate the effect of the inter-population database in 100 paternity trios with no inconsistencies at 23 STRs. Subjects and methods 100 paternity trios were evaluated considering inter-population allelic frequency values for calculation of Combined Paternity Index (CPI) and Probability of Paternity (POP). Results No significant variation (p < 0.05) among the allele frequencies at the interpopulation level was observed. The number of obligate alleles and the likelihood of transferring obligate alleles from the putative father showed a positive correlation (p < 0.005) with Power of Discrimination (PD), Polymorphic Information Content (PIC), Power of Exclusion (PE), Paternity Index (PI), Observed and Expected Heterozygosity (Ho and He), and a statistically significant negative correlation (p < 0.005) with Matching Probability (Pm). The average Combined Paternity Index (CPI) and Probability of Paternity (POP) did not show any statistically significant difference (p < 0.05) at the interpopulation level. Conclusion The allelic database showed no effect on the CPI and POP in 100 paternity trios. This suggests no urgent need for using population-specific databases for statistical evaluation of paternity trios without inconsistencies.